Structural stabilization of the intrinsically disordered SARS-CoV-2 N by binding to RNA sequences engineered from the viral genome fragment - Sara Landeras-Bueno; Chitra Hariharan; Ruben Diaz Avalos; Andrew S. Norris; Dalton T. Snyder; Kathryn M. Hastie; Stephanie Harkins; Michelle Zandonatti; Roshan R. Rajamanickam; Eduardo Olmedillas; Robyn Miller; Sujan Shresta; et al. (Nature Communications)
Abstract The nucleocapsid N is one of four structural proteins of the coronaviruses. Its essential role in genome encapsidation makes it a critical therapeutic target for COVID-19 and related diseases. However, the inherent disorder of full-length N hampers its structural analysis. Here, we describe a stepwise method using viral-derived RNAs to stabilize SARS-CoV-2 N for EM analysis. We identify pieces of RNA from the SARS-CoV-2 genome that promote the formation of structurally homogeneous N dimers, intermediates of assembly, and filamentous capsid-like structures. Building on these results, we engineer a symmetric RNA to stabilize N protein dimers, the building block of high-order assemblies, for EM studies. We combine domain-specific monoclonal antibodies against N with chemical cross-linking mass spectrometry to validate the spatial arrangement of the N domains within the dimer. Additionally, our cryo-EM analysis reveals novel antigenic sites on the N protein. Our findings provide insights into N protein´s architectural and antigenic principles, which can guide design of pan-coronavirus therapeutics.